2016
DOI: 10.1590/1519-6984.20015
|View full text |Cite
|
Sign up to set email alerts
|

Variability study of entomopathogenic nematode populations (Heterorhabditidae) from Argentina

Abstract: Entomopathogenic nematodes (EPN) belonging to the Heterorhabditidae family are lethal parasites of soil-dwelling insects. Two species were reported in Argentina: Heterorhabditis argentinensis and Heterorhabditis bacteriophora characterized mainly by morphometric features. In this work a comparative and phylogenetic study between five Heterorhabditis populations from Argentina was conducted to analyze the variability between strains and to evaluate the taxonomic position of Heterorhabditis argentinensis. The PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…These variations were found to be independent of the developmental stages and the collection localities of soil samples. It was evident from the previous studies that there were large intraspeci c variations present among the nematodes which were also observed among present isolates of the present investigation (Achinelly et al, 2017;Dolinski et al, 2008). However, less intraspeci c variations were observed between CH25 and CH26 as they formed groups (ellipses) in all studied stages.…”
Section: Discussionsupporting
confidence: 76%
“…These variations were found to be independent of the developmental stages and the collection localities of soil samples. It was evident from the previous studies that there were large intraspeci c variations present among the nematodes which were also observed among present isolates of the present investigation (Achinelly et al, 2017;Dolinski et al, 2008). However, less intraspeci c variations were observed between CH25 and CH26 as they formed groups (ellipses) in all studied stages.…”
Section: Discussionsupporting
confidence: 76%
“…Synonymized by Hominick (2002) based on molecular evidence provided by Adams et al (1998) . Synonymization status is supported by molecular data of Phan et al (2003) and Achinelly et al (2017) .…”
Section: Resultsmentioning
confidence: 68%
“…This is consistent with the findings of Morales et al (2016), who observed differences between Venezuelan populations of H. amazonensis, and Poinar (1993) and Stock et al (1996), who reported intraspecific differences among species of Steinernematidae. Achinelly et al (2017), evaluating the morphometric characteristics of Heterorhabditis bacteriophora VELI and H. argentinensis isolated from different regions of Argentina, observed that the isolates obtained in regions with more rainfall and humidity had larger dimensions. According to these authors, the juvenile phase (JIs) has the least variability and is the best option for the morphological comparison of different Heterorhabditis populations.…”
Section: Morphometric Characterizationmentioning
confidence: 99%